"I'm Not Going Home With a Catheter": Patient-Perceived Outcomes Associated With Perioperative Intermittent Catheterization. Issue 12 (26th December 2022) - Shinnick, Julia K.; Raker, Christina A.; Geller, Elizabeth J.; Rardin, Charles R.; Cooper, Anne C.
Abstract : Importance: Indwelling catheters are a known source of dissatisfaction for postoperative patients. There is a paucity of data describing patient-perceived outcomes associated with the alternative of intermittent self-catheterization (ISC). Objectives: The aim of this study was to describe patient satisfaction and outcomes associated with ISC after outpatient female pelvic reconstructive surgery. Study Design: This was a secondary analysis of a prospective cohort study at an academic tertiary referral center from September 2018 to June 2021. Participants completed preoperative ISC instruction that included an instructional video, 1:1 demonstration with a health care provider, and provision of ISC supplies. Participants were instructed to perform ISC postoperatively until they had 2 consecutive outpatient PVRs less than one-half the voided volume. Participant satisfaction was assessed 2 weeks postprocedure, with adverse events evaluated at 6 weeks. Results: One hundred sixty participants completed preoperative ISC instruction and were included in this analysis. Mean age was 52.1 (SD +/− 11.4) years, mean body mass index was 28.9 (SD +/− 5.8), and mean time from ISC instruction to surgery was 16.4 (SD +/− 15.7) days. Most participants reported no difficulty with ISC (124/160 [78%]) and had high levels of satisfaction (148/151 [98%]). Difficulty performing ISC was not associated with time since ISC instruction ( P = 0.32), difficulty noted at ISC instruction by the health care provider ( P = 0.24), or the duration of ISC instruction ( P = 0.16). On multiple logistic regression, age, body mass index, and prolapse beyond the hymen did not predict difficulty learning or performing ISC. At 6 weeks postprocedure, 22 of 155 participants (14%) endorsed symptoms of a urinary tract infection, and 15 of 160 (9%) had a culture-proven urinary tract infection. Conclusions: Women undergoing outpatient pelvic reconstructive surgery report ease and satisfaction with ISC.